The Impact of FOMO on The Hedonism Attitude of Generation Z In Islamic Consumption Behavior - Evi Fadhilatul Istiqomah; Amin Wahyudi (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2024)
This study discusses the impact of the Fear of Missing Out (FOMO) phenomenon on hedonistic attitudes in Generation Z's consumption behavior, focusing on the context of Islamic economics. The 20th century witnessed technological advances that brought significant changes in people's lifestyles, especially among Generation Z who are always connected to social media. This encourages excessive consumer behavior, which can be seen as a response to social pressure to keep up with trends. This study identifies that FOMO encourages individuals to adopt a hedonistic lifestyle, which prioritizes temporary satisfaction over long-term considerations. A literature analysis approach is used to explore the relationship between FOMO, hedonism, and Islamic consumption principles. The results show that the application of Islamic values, such as justice and moderation, can help Generation Z manage their consumption behavior, avoid waste, and find a balance between material and spiritual needs. These findings are expected to provide insight for the younger generation to develop more responsible and sustainable consumption patterns.